(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The research describes how religion served as a notable element for the realization of field work in a diagnosis in which I participated in 2012 on citizen security, carried out in the Oblatos de Guadalajara neighborhood, Jalisco, which was carried out by a municipal public security institution . Project whose aim was to eradicate the situation that the colony was experiencing: insecurity, gang activity, violence, consumption and sale of drugs; and that through the application of workshops, it is allowed to recover each of the public spaces in the area, with the public as a participant for the facilitation of these complications. The writing tells of the obstacles and the facilities that we face in this intervention for the approach with the study actors and generate empathy, in order to carry out the field work to comply with the investigation.